Potencial de armazenamento de água no caule de plantas do bioma caatinga - Tillesse, Francisco Esmayle Alves de (2017)
The hydrological processes occurring in forest are influenced mainly by the existing plant species and their physiological characteristics. Water consumption by these plant communities has been considered an important issue in studies of water availability. Thus, this work had as general objective to analyze the water storagepotential in the stem in representative plants of the Caatinga biome. Data collection in the field was performed in the Aiuaba Experimental Basin (BEA), with a total area of 12 km², located entirely within the Ecological Station of the Chico Mendes Institute (ESEC - Aiuaba), the largest federal conservation unit jot the Caatinga biome, located in the municipality of Aiuaba, Ceará. For the development of this research was carried out a phytosociological survey, a survey of the spatial distribution of wood density stem storage water capacity. Data from the active xylem area were related to wood anatomy, diameter at breast height (DBH), total height and volume. Allometric models were developed to estimate the area of the active xylem. Statistical analysis was performed through regression analysis of variance, coefficient of determination and descriptive statistics. Regarding the floristic survey thirteen species and eight botanical families were registered. The families Euphorbiaceae (78%) and Fabaceae (7%) presented the highest number of species covering 85% of the total inventories. The results of the study show that the two species (quince and catingueira) analyzed have different characteristics that influence the transport of water in the plant. The marmeleiro (CrotonsonderianusMull) and catingueira (PoicianellapyramidalisTul.) Are the species that holds the highest density of plants per hectare, reaching 85% of the total number of species listed. The potential model fitting represented the relationship between the stem area and the hydrodynamic xylem for the two analyzed species. The water content in the stem of a catingueira plant is about five times greater than that of a quince plant. However, due to the greater occurrence in the area, the water retained in the stem of quince plants (per hectare) is about twice the amount retained incatingueiraplants. Despite 40 years of conservation of the ESEC of Aiuaba, the area is still in the second stage (shrub) of the secondary succession stage evidenced by the greater occurrence of species of the genus Croton, present in soils with good physical and chemical characteristics, being an indicator of secondary succession of recovery.